Implementation of Arabic Language Learning With School-Based Management - Taufiq Nur; Azhar Arsyad; Kamaluddin Abu Nawas; Amrah Kasim; Suriyati Suriyati; Makmur Jaya Nur (Prodi Manajemen Pendidikan Islam Institut Pesantren KH Chalim Mojokerto, 2024)
This research aims to describe the concept of implementing Arabic language learning with school-based management at Madrasah Aliyah Negeri 1 Bulukumba. The method used in this research is field research. The results of this research concluded that the concept of implementing Arabic language learning with school-based management at Madrasah Aliyah Negeri 1 Bulukumba was implemented through several strategies, namely listening skills (Istima) which were implemented through several activity steps, namely determining Istima' materials according to the theme to be taught, determining concepts relevant to istima. Meanwhile, the reading proficiency strategy (qira'ah) is implemented by the teacher reading Arabic texts well and correctly and also translating them, then students listen carefully. The skills in writing (kitabah) are carried out by the Arabic language study teacher by showing several sentences on the blackboard, then the students read and pay close attention for a few moments. Then the material is removed, then dictated, and students write into notebooks what the teacher dictates. For speaking skills (kalam), the Arabic language study teacher starts by pronouncing new vocabulary (mufrodat) one by one by the language study teacher and then imitates all the students.